Image of Health in Adolescents with Mental Retardation and Oligophrenia - T.A., Kovelina; T.S., gutova; V.M, Marukhno; A.A., Rykova; S.A., Pogosyan (International Journal of Psychosocial Rehabilitation, 2020)
An empirical study of the health image of adolescents with oligophrenia and mental retardation has been carried out. The obtained results are analyzed on the basis of the psychodiagnostic complex. It is shown, with the primary support on what formative of consciousness is formed the image of health in adolescents. 68 adolescents took part in the empirical study in 3 experimental groups: adolescent with DSD, adolescent with a diagnosis of mild mental retardation and group norms adolescent. We used the following psychological techniques: projective drawing technique on the theme "My health", "self-Esteem" Dembo-Rubinstein, alloy De Greefe (modified version), "Color test of relations" by Etkind and also studied were offered an open-ended question "What is health?". Assessment of adolescents with DSD and those with mental retardation is inadequate and suggests that they are not aware of existings defect. Adolescents with mental retardation perform drawings, usually based on a sensual tissue of subject content, which confirms the fact that the backlog in the formation of the myth health and sense of health. Mentally retarded teenager is at an embryonic stage of formation, in the form of health there is only sensual tissue.